Diplomado de Recipientes a Presión: Módulo V (Clasificaciones de Soldadura Conforme a la Sección IX del Código ASME) - Rivera Mendoza, Orlando R. (My University, 2007)
A welding symbol consists of basic elements. These elements can be joined in various combinations to denote any type of weld needed for any type on joint. The condensed summary presented here identifies these elements and will serve as a ready reference for those associated whit a welding program.
Keywords: Recipientes a presión; Welding, groove weld, saw, FCAW, fillet weld, joint, tension, bend, welder, WPQ, recertification, macro-etching, pipe, plate